Peningkatan Kemampuan Komunikasi Melalui Metode Bermain Peran di Sekolah Dasar - masriani, masriani; marbela, lilis (Jurnal Edukasi, 2023)
Problems that exist in learning in general are ineffective communication either between teachers and students, or between students and students. One of the efforts made by teachers is the application of various learning methods, one of which is the role playing method. From observations made on students, students' communication skills increased by 90% and were categorized as very good because they were in the 81%-100% interval. Based on theoretical studies and observation results that have been carried out by researchers, which influence the increase in students' communication skills in class V A of State Elementary School 010 Dialihan Kec. Keritang is the use of role playing methods